Implementasi Robot Manipulator menggunakan Sinyal Electromyography berdasarkan Pergerakan Kaki Manusia - Moch. Afandi Yusup; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The purpose of this research is to determine whether the students 'computational thinking skills have an influence on students' learning motivation. This descriptive quantitative research was followed by 80 respondents to fill out essay answer sheets and questionnaires while collecting data by analyzing problem solving thinking, logical thinking, structured thinking, and creative thinking. The need for procedures in designing the right design requires high imagination to generate creative ideas. In measuring it, data was collected in the form of a computational thinking essay test and a questionnaire for learning motivation. Based on the results of the research, it shows that the computational thinking test essay test shows the overall mean result of 56.75 if the percentage is 71% of 80 students and the results of the motivation using the questionnaire produce a mean of 72.29 if the percentage is 90% of 80 students. The results of the t-test analysis showed a significance value of -9,118 <1,994 for computational thinking and 0.001 <0.05 for motivation, which means it fulfills and it can be concluded that there is a relationship between computational thinking on learning motivation with the effect of 9.2% of the results obtained from the study.